Biochemical markers in COVID-19. A literature review (Research, Society and Development, 2021)
The pandemic caused by COVID-19 presented several challenges for the medical, research and public health services communities. For this reason, knowledge about the biochemical profile of those infected is extremely important, since it can help in the diagnosis and treatment of possible complications. The aim of the present study is to perform a literature review capable of demonstrating the biochemical markers of positive or negative COVID-19 patients based on the results of routine blood tests in publications. For its development, an electronic search was performed in the databases Scielo, Pubmed, Science Direct and Google Scholar. The results of this review demonstrated the importance of amplifying viral RNA by RT-PCR, as it can be used as a standard for confirming the infection that detects nucleic acid. However, other markers are observed as thresholds for AST and LDH that allowed predicting a prognosis of complications in COVID-19-positive or negative patients based on the results of routine blood analysis. The blood test can be used as an alternative to RT-PCR in monitoring the worsening of COVID-19 positive patients. Biochemical changes are not yet fully understood. Thus, it is concluded that it is extremely important to know the biochemical changes that may be associated with infection by the SARS-CoV 2 virus, which can assist in the prognosis of COVID-19 and the choice of the best treatment for possible complications.